Solutions for Improving the Economic Efficiency of Koi Carp Intensive Aquaculture Considering Different Technological Scenarios - Aurelia NICA1; Alina MOGODAN1; Ira A. SIMIONOV1; 3; Stefan M. PETREA1; Dragos S. CRISTEA2; Mihaela NECULITA2; Sarina ROSENBERG2; Victor CRISTEA3 (Communications of International Proceedings, 2020)
The aim of present study is to evaluate the effect of 4 significant different feeding rates (V1 – 0.22%, V2 – 0.12%, V3 – 1.22%, respectively V4 – 1%) on koi carp rearing and economic sustainability performances in order to determine proper feeding technologies that addresses to certain technological scenario. The experimental trials were carried out during a 41 days experimental period. The experimental design was made in duplicate. The water quality parameters (water temperature, pH, and dissolve oxygen) were evaluated daily during the entire experimental trials. The average individual biomass was 28±1.2 grams and the average individual length was 11±0.5 cm. Considering the registered values of SGR, FCR and RGR, it can be stated that V1 and V2 feeding rates are recommended for koi carp stocking, during a longer period of time, while V3 and V4 feeding rates can be also applied for rearing purposes. From an economic point of view it is recommended not to use, on a long-term, the V1 and V2 technological scenario, since they do not offer economic sustainability. These scenarios are recommended to be used only during limited period of time, if certain dysfunctionalities develops during the fish rearing technological process. If koi carp rearing is targeted, the V4 scenario is identified as most suitable in order to be used for assuring the best results in terms of production (FCR value) and economical sustainability. However, the results of this present study are influenced by the PRAS performance to sustain a certain degree of production intensity, limited by the configuration and design of water conditioning units.
Keywords: Economic Sustainability; Feeding Rates; Intensive Aquaculture; Koi Carp.